Obstructive Jaundice - Ahmad, Ijaz; Jan, Atta Ullah; Ahmad, Rizwan (Journal of Postgraduate Medical Institute, 2011)
this prospective study includes 107 cases admitted to surgical A unit of KTH Peshawar. All the information, admission till discharge, was recorded on a proforma. There were 44 male and 63 female patients. In males the causes of obstructive jaundice included slightly higher number of malignancies than stone in females, the more common cause was the presence of gall stones. Overall, the commoner cause was gall stones. Majority ofthese cases with common bile duct stones could have been treated with a laparoscope or an endoscope were these modalities available. Teh common operative procedures adopted were choledochoduodenostomy or choledocholithotomy, followed by T tube Drainage.